Manajemen Kantor di PT Indonesia Power Unit Pembangkit Suralaya - Giyanti, Sri (Utilitas, 2015)
Research intended to describe office management covered: administration activities, planning, work systemcontrol, office products, facilities and infrastructures of Public Relation and Human Resource Department of PTIndonesia Power Unit Pembangkit Suralaya, Banten Province, Indonesia. The Case study Qualitative methodimplemented in this study. Data collected by observation, interviews, document analysis. Data validated bytrianggulation process, including technique trianggulation and resource trianggulation. The data analyzedthrough data reduction, data display and data verification. Result of the study showed the various implementationof office administration at Public Relation and Human Resource Department od PT Indonesia Power UnitPembangkit Suralaya as: organizational structure shape as the mixture between line, staff and functional;planning process acquired from central office; the various official products here as correspondence, notes,archiving, internal forms, information dissemination. The facilities and infrastructures well managed.AbstrakPenelitian bertujuan untuk mengetahui manajemen kantor di PT Indonesia Power Unit PembangkitSuryalaya, meliputi: pengorganisasian kantor, perencanaan dan pengawasan sistem kerja, produk-produkperkantoran, peralatan kerja kantor dan lingkungan kantor di bagian SDM dan Humas pada PT Indonesia PowerUnit Pembangkit Suralaya yang berlokasi di Banten, Indonesia. Metode yang digunakan ialah metode kualitatifstudi kasus. Teknik pengumpulan data dengan cara observasi, wawancara, analisis dokumentasi. Data divalidasidengan trianggulasi teknik dan trianggulasi sumber. Teknik analisis data antara lain melalui proses reduksi data,display dan verifikasi data. Hasil penelitian menunjukkan bahwa struktur organisasi yang dipakai berbentukcampuran gabungan dari lini, staff dan fungsional; perencanaan dilakukan oleh kantor pusat PT IndonesiaPower; produk-produk perkantoran beragam jenisnya seperti membuat surat, membuat catatan lalu diarsipkan,membuat formulir intern untuk karyawan, serta memberikan informasi; peralatan kerja kantor meliputi mesinkantor dan perkakas kantor, dan lingkungan fisik kantor sangat diperhatikan.